2015
DOI: 10.1089/ten.tea.2013.0720
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Differentiation and Delivery of Mouse Retinal Progenitor Cells Using a Micropatterned Biodegradable Thin-Film Polycaprolactone Scaffold

Abstract: The deterioration of retinal tissue in advanced stages of retinitis pigmentosa and age-related macular degeneration and the lack of signaling cues for laminar regeneration are significant challenges highlighting the need for a tissue engineering approach to retinal repair. In this study, we fabricated a biodegradable thin-film polycaprolactone (PCL) scaffold with varying surface topographies using microfabrication techniques. Mouse retinal progenitor cells (mRPCs) cultured on PCL scaffolds exhibited enhanced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 46 publications
0
33
1
Order By: Relevance
“…Although traditional microfabrication techniques offer precise control of pore size and distribution, resolution can limit pore size and spacing [17, 3436]. In addition, even if one uses microfabrication to form sub-cellular structures, creating a truly three-dimensional scaffold with horizontal pores for nutrient diffusion in addition to vertical channels is challenging [37, 38]. Furthermore, the efficiency of traditional microfabrication is usually dependent on the use of silicon oxide or silicone rubber templates, meaning that one cannot easily adjust the overall scaffold design after they create the template.…”
Section: Discussionmentioning
confidence: 99%
“…Although traditional microfabrication techniques offer precise control of pore size and distribution, resolution can limit pore size and spacing [17, 3436]. In addition, even if one uses microfabrication to form sub-cellular structures, creating a truly three-dimensional scaffold with horizontal pores for nutrient diffusion in addition to vertical channels is challenging [37, 38]. Furthermore, the efficiency of traditional microfabrication is usually dependent on the use of silicon oxide or silicone rubber templates, meaning that one cannot easily adjust the overall scaffold design after they create the template.…”
Section: Discussionmentioning
confidence: 99%
“…However, these cells have low integration efficiency into the brain circuitry, which may prevent long‐term positive outcomes. In recent years, studies have started focusing on using scaffolds in order to direct cells toward specific lineages . Additional studies have shown improvement of cell adhesion as well as differentiation of retinal progenitor cells seeded on polymeric scaffolds in a retinal degeneration model .…”
Section: Discussionmentioning
confidence: 99%
“…As it has been stipulated that injected adherent cells cannot survive in the absence of a substrate,17 most implants employed the use of a resorbable scaffold to restitute cells into a tissue before transplanting it into the subretinal layer. Below are some of the methods reported, including cell sheet approach and scaffold-based approach.…”
Section: Bm Te Approachesmentioning
confidence: 99%